2022
DOI: 10.1108/mip-02-2022-0081
|View full text |Cite
|
Sign up to set email alerts
|

Luxury consumption amidst the COVID-19 pandemic

Abstract: PurposeThis study investigates shifts in luxury consumers' perceptions regarding luxury consumption, subsequent changes in the meaning of luxury and antecedents of luxury observed amidst the COVID-19 pandemic.Design/methodology/approachOverall, 145, one-to-one qualitative interviews were conducted online with luxury consumers and the data acquired was analysed using NVivo.FindingsPhygital connectedness and access-based consumption are the future of luxury for luxury consumers' well-being, social connectedness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The literature review suggested that the pandemic has led to changes in luxury consumption in several ways. Based on the first theme of digitalization and innovation, logical solutions to the plummeting sales of luxury products involve embracing new technologies (Kumar, 2023). However, the second theme of consumer behavior revealed that COVID-19 has given a new meaning to luxury, from a material possession to life and experience (Loranger & Roeraas, 2022).…”
Section: Transformational Shifts In Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…The literature review suggested that the pandemic has led to changes in luxury consumption in several ways. Based on the first theme of digitalization and innovation, logical solutions to the plummeting sales of luxury products involve embracing new technologies (Kumar, 2023). However, the second theme of consumer behavior revealed that COVID-19 has given a new meaning to luxury, from a material possession to life and experience (Loranger & Roeraas, 2022).…”
Section: Transformational Shifts In Behaviormentioning
confidence: 99%
“…Social responsibility issues were also discussed in several papers related to luxury products during the COVID‐19 pandemic (Bae, 2023; Batat, 2021; Blancheton, 2021; Cvik & Pelikánová, 2021; Kumar, 2023; Pelikánová et al, 2021). According to Kumar (2023), COVID‐19 has transformed the meaning of luxury from the consumers' inner selves to a broader scope–social empathy as luxury consumers are aware of the human suffering experienced by society during the pandemic. Luxury consumers also lay more emphasis on intimacy and social connectedness to be fulfilled by the luxury products to generate happiness, emotional bond, and support during the crisis.…”
Section: Sectoral Analysismentioning
confidence: 99%
See 3 more Smart Citations